Harnessing the Power of Digital Twins: A Paradigm Shift in Precision Medicine and Cancer Biology - Butt, Warda Ali; Iqbal, Muhammad Javed; Hameed, Simran Abdul; Amin, Ghanima; Khalid, Arwa; Aslam, Affaf; Hussain, Sajid (Indus Journal of Bioscience Research, 2025)
In recent years, the potential use of digital twins (DTs) in healthcare sectors is becoming a growing research area that can lead to more individualized patient care. In this regard the use of precision medicine towards personalized treatment is emerging as promising approach that takes into account of individual variability in genes, environment and lifestyle of each person. Moreover, precision medicine provides a framework for designing a targeted treatment for individual patients by combining clinical and demographic information as well as biomarkers and medical imaging data. The process of diagnosing and treating patients, particularly in the context of cancer treatment, involves multiple steps and can also have certain limitations. Introducing DTs in personalized treatment planning, including the use of precision medicine, could support and enhance the cancer care. Although the digital twin model has the potential to accurately diagnose cancer, advanced monitoring systems are necessary for commercial use.